Carbon-Based Coatings in Medical Textiles Surface Functionalisation: An Overview - Antunes, José (2021)
The COVID-19 pandemic has further highlighted the need for antimicrobial surfaces, especially those used in a healthcare environment. Textiles are the most difficult surfaces to modify since their typical use is in direct human body contact and, consequently, some aspects need to be improved, such as wear time and filtration efficiency, antibacterial and anti-viral capacity, or hydrophobicity. To this end, several techniques can be used for the surface modification of tissues, being magnetron sputtering (MS) one of [hose that have been growing in the last years to meet the antimicrobial objective. The current state of the art available on textile functionalisation techniques, the improvements obtained by using MS, and the potential of diamond-like-carbon (DLC) coatings on fabrics for medical applications will be discussed in this review in order to contribute to a higher knowledge of functionalized textiles themes.